Microwave-Assisted Extraction of Natural Antioxidants from the Exotic Gordonia axillaris Fruit: Optimization and Identification of Phenolic Compounds - Ya Li; Sha Li; Sheng-Jun Lin; Jiaojiao Zhang; Cai‐Ning Zhao; Hua‐Bin Li (2017)
Our previous study reported that the fruit of Gordonia axillaris , an edible wild fruit, possessed strong antioxidant activity. In this study, a microwave-assisted extraction (MAE) method was established to extract antioxidants from the fruit of Gordonia axillaris . The influence of five parameters, including ethanol concentration, solvent/material ratio, extraction time, extraction temperature and microwave power, was investigated by single-factor experiments. Three factors, namely ethanol concentration, solvent/material ratio, extraction time, were found to exert a major influence on extraction efficacy, and were further studied by response surface methodology to investigate their interactions. Ethanol concentration of 36.89%, solvent/material ratio of 29.56 mL/g, extraction time of 71.04 min, temperature of 40 °C, and microwave power of 400 W were found to be the optimal condition. The TEAC value was 198.16 ± 5.47 µmol Trolox/g DW under the optimal conditions, which was in conformity to the predicted value (200.28 µmol Trolox/g DW). In addition, the MAE method was compared with two conventional methods (Soxhlet extraction and maceration extraction). Results showed that the antioxidant capacity of the extract obtained by MAE method was stronger than that obtained by maceration (168.67 ± 3.88 µmol Trolox/g DW) or Soxhlet extraction (114.09 ± 2.01 µmol Trolox/g DW). Finally, several phenolic compounds in the extract were identified and quantified by UPLC-MS/MS, which were rutin, gallic acid, protocatechuic acid, epicatechin, epicatechin gallate, 2-hydrocinnamic acid, p -coumaric acid, quercetin, chlorogenic acid and ferulic acid.